Workplace Deviance and Its Organizational Antecedents: A Dual Mediation Model in the Context of Islamic Universities - Putri Nilam Kencana; Nani (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: One technique to increase human independence is through education; however, this will have an impact since the workplace may react negatively to these elements by engaging in deviant conduct. With organizational commitment and job satisfaction serving as mediating factors, this study looks at how workplace spirituality, organizational justice, and ethical leadership can lessen deviant conduct in the workplace. Methodology: This study was carried out in the field of education, particularly at academic institutions. In order to gather data for this qualitative study, a questionnaire was employed. In this study, 225 respondents were chosen from three Islamic universities in West Java using the quota sample approach. The Smart Partial Least Square (SmartPLS) tool was utilized for the analysis in this study. Findings: The findings demonstrated that workplace spirituality, ethical leadership, and organizational commitment had a significant and negative impact on deviant behavior in the workplace, whereas job satisfaction and organizational justice had a negative and negligible impact. Subsequent research revealed that ethical leadership and workplace spirituality significantly and favorably impacted organizational commitment, whereas job satisfaction was positively impacted by organizational justice. Other results show that organizational commitment mediates the association between ethical leadership and workplace spirituality and that organizational commitment mediates the relationship between ethical leadership and workplace deviant conduct. Furthermore, the relationship between workplace deviant behavior and organizational justice cannot be mediated by job satisfaction. Implications/Novel Contribution: Educational institutions, especially Islamic universities, may integrate ethical leadership standards into hiring and performance evaluation criteria. The results support the need for formal policies promoting organizational justice, including fair workloads, transparent promotion systems, and grievance-handling procedures. Institutions should adopt employee well-being and spirituality frameworks as part of their human-resource policies to enhance organizational commitment and reduce behavioral risks.